Effectiveness and cost-effectiveness of RSV infant and maternal immunization programs: A case study of Nunavik, Canada. (November 2021) - Nourbakhsh, Shokoofeh; Shoukat, Affan; Zhang, Kevin; Poliquin, Guillaume; Halperin, Donna; Sheffield, Holden; Halperin, Scott A.; Langley, Joanne M.; Moghadas, Seyed M.
Abstract: Background: Despite passive immunization with palivizumab to select high-risk children under two years of age, the health and economic burden of respiratory syncytial virus (RSV) remains substantial. We evaluated the effectiveness and cost-effectiveness of immunization programs with new generations of RSV prophylactics, including long-acting monoclonal antibodies (LAMA) and maternal vaccines, in terms of reducing hospitalizations in Nunavik, a Canadian Arctic region. Methods: We developed an agent-based model of RSV transmission and parameterized it with the demographics and burden of RSV in Nunavik, Québec. We compared various immunization strategies, taking into account the costs associated with program delivery and calculating the incremental cost-effectiveness ratio (ICER) using quality-adjusted life-years (QALYs) gained as a measure of effectiveness. Scenario analyses included immunization with palivizumab and LAMA for infants under one year of age, and maternal vaccination in mild, moderate, and severe RSV seasons. Data were analysed from November 1, 2019 to May 1, 2021. Findings: We found that a Nunavik pilot program with palivizumab which included healthy full-term infants aged 0–2 months in addition to those considered high-risk for complicated RSV disease is not cost-effective, compared to offering palivizumab only to preterm/chronically ill infants under 1 year of age. Using LAMA as prophylaxis produces ICER values of CAD 39, 414/QALY (95% Credible Interval [CrI]: 39, 314–40, 017) in a mild season (moderately cost-effective) and CAD 5, 255/QALY (95% CrI: 5, 222–5, 307) in a moderate season (highly cost-effective). LAMA was a dominant (cost-saving with negative incremental costs and positive incremental effects) strategy in a severe RSV season. Maternal vaccination combined with immunization of preterm/chronically ill infants 3–11 months was also a dominant (cost-saving) strategy in all seasons. Interpretation: The switch from palivizumab in RSV immunization programs to new prophylactics would lead to significant savings, with LAMA being an effective strategy without compromising benefits in terms of reducing hospitalizations. Funding: This work was funded by the Canadian Institutes of Health Research and the Public Health Agency of Canada through the Canadian Immunization Research Network.